A Study on Peripheral Neuropathy and Its Related Risk Factors Associated With hba1c Levels (Journal of Bio-Science, 2021)
Diabetic peripheral neuropathy (DPN) patients frequently feel persistent pain, which is described as painful diabetic peripheral neuropathy (PDPN), which begins in both feet and frequently spreads to the calves, fingers, and hands. PDPN not only causes pain, but also affects patients' sleep, emotions, mental state, and everyday activities, resulting in a low quality of life and a significant financial burden. The goal of this study was to monitor if there was a link between the prevalence, pattern, and related risk factors of diabetic peripheral neuropathy and hemoglobin A1C (HbA1c) levels. In this crosssectional study, 150 type-2 diabetic patients were screened for DPN with PDPN and their HbA1c level was measured in every three months. DPN, PDPN and non-painful DPN were confirmed in patients displaying both clinical manifestations of neuropathy and neurological abnormalities assessment. DPN was detected in 24% (n = 36), while PDPN was found at 15% (n = 23) of the total patients. The prevalence of PDPN is 63.88% (n = 23) and non-painful DPN is 36.11% (n = 13) of total DPN (n = 36). Out of total PDPN (n = 23), the prevalence of symmetrical pain is 65% (n = 15), asymmetrical 35% (n = 8), sensory 26% (n = 6), motor 13% (n = 3), mixed (sensorimotor) 61% (n = 14), lower limb involvement 48% (n = 11), upper limb13% (n = 3) and both limb 39% (n = 9). In comparison to patients without DPN, both PDPN and non-painful DPN, patients had greater HbA1c levels (p